Traducción y validación de la Escala de Actitudes hacia la Investigación Revisada (R-ATR) en estudiantes universitarios peruanos - Loayza-Rivas, José (2023)
This study aimed to translate and validate the Revised Attitudes Toward Research Scale (R-ATR; Papanastasiou, 2014) in Peruvian university students. A total of 214 students participated, 65.9% female, with a mean age of 24.79 years (SD = 5.15), from a private university in Metropolitan Lima. A Confirmatory Factor Analysis (CFA) was performed to test the R-ATR model of three correlated factors, obtaining an acceptable fit. On the other hand, excellent reliability coefficients for internal consistency and appropriate evidence of content validity were obtained. It is concluded that this Spanish version of the R-ATR has adequate evidence of validity and reliability that accredits its use in the Peruvian context.